Analisis Pemahaman Guru-Guru SMK Jurusan Akuntansi tentang Materi Rekonsiliasi Fiskal dan Pengisian e-SPT Tahunan Sesuai Materi UKK: Studi Deskriptif Guru-Guru MGMP Akuntansi di Kabupaten Agam dan Kota Bukittinggi - Herlina Helmy; Charoline Cheisviyanny; Sany Dwita; Vanica Serly; Nayang Helmayunita (Universitas Negeri Padang, 2018)
The Academic Year 2016/2017 was the first year of fiscal reconciliation and filling an Annual Tax Returns as the material of Competency and Skills Exam of Vocational School students. Students are required to understand and can calculate the amount of tax payable and filling in annual tax returns, then they can work on the questions properly and correctly. This student's ability is inseparable from the teacher's ability to understand the material. Therefore, the teachers is required to have deep knowledge and understanding about the material. The purpose of this activity is to conduct training to improve the understanding and knowledge of the Vocational School Teachers of Accounting Departments on Fiscal Reconciliation Materials and the Filling of Annual E-Tax Return in accordance with Competency and Skills Exam Materials in Agam District and Bukittinggi City, West Sumatra. The training was carried out for 4 days in 2 weeks. Based on the results of the assessment from the pretest and posttest was conducted to the participants, shows that there was an increase in the understanding of vocational school teachers in the accounting department for annual fiscal reconciliation and E-Tax Return materials for individual taxpayers and corporate taxpayers. The results of the survey conducted with a questionnaire to find out the perceptions of participants regarding the usefulness of the community service activities, it shows that the training participants were very enthusiastic and get benefit from this activity.Keywords: teachers, SMK, understanding, fiscal reconciliation